1970
DOI: 10.1136/jcp.23.8.703
|View full text |Cite
|
Sign up to set email alerts
|

Folate binders in body fluids

Abstract: SYNOPSIS In normal serum, saline dialysis for 48 hours in Visking casing resulted in folate clearance closely comparable to that produced by haemoglobin-coated charcoal adsorption, except in kwashiorkor where charcoal removed a greater proportion of folate. Pre-and post-dialysis values probably represented total and bound folate, respectively. Urinary folate consisted almost exclusively of dialyzable or free folate. Folate in saliva, bile, and erythrocytes consisted of dialyzable and non-dialyzable fractions; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
9

Year Published

1971
1971
1985
1985

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 10 publications
1
14
0
9
Order By: Relevance
“…On the other hand, the FAA attached to protein fractions seems to be firmly bound, since it tolerates, e.g., an ammonium sulphate precipitation and repeated gel filtrations without abandoning its attachment to the corresponding proteins [unpublished data], FAA recovery in these cases was nearly 100%. Similar results concerning the occurrence of FAA in-and outside the protein band have been reported by Retief and H uskisson [6,7], Their absorption studies with charcoal pre parations coated with molecules of varying size suggested that the main serum folate binder is of molecular weight 70,000-120,000. Since the mole cular weight of albumin is 69,000, it seems probable that the conclusion of these authors concerning the FAA-carrying protein agrees with our finding.…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, the FAA attached to protein fractions seems to be firmly bound, since it tolerates, e.g., an ammonium sulphate precipitation and repeated gel filtrations without abandoning its attachment to the corresponding proteins [unpublished data], FAA recovery in these cases was nearly 100%. Similar results concerning the occurrence of FAA in-and outside the protein band have been reported by Retief and H uskisson [6,7], Their absorption studies with charcoal pre parations coated with molecules of varying size suggested that the main serum folate binder is of molecular weight 70,000-120,000. Since the mole cular weight of albumin is 69,000, it seems probable that the conclusion of these authors concerning the FAA-carrying protein agrees with our finding.…”
Section: Discussionsupporting
confidence: 75%
“…Normal human plasma contains 6 to 20 ng of FA per ml (24), most of which is nonspecifically protein bound and freely dialyzable (16). The PABA concentration of normal human plasma varies greatly but is generally less than 1.0 ng/ml (R. Desjardins, unpublished observations).…”
mentioning
confidence: 99%
“…It has been suggested that this might be due to hormonally in duced synthesis of folate binder as it also occurred in women taking oral contra ceptives (6). As mentioned earlier, serum folate decreased during pregnancy and as the urinary folate excretion was higher in pregnant than in non-pregnant women, it was therefore postulated that urinary loss of folate could be one factor contri buting to the fall of serum folate activity (13)(14)(15). In order to compensate for the loss of high urinary folate and the greater demand of folate during pregnancy, the body therefore increased synthesis of serum FABP for binding the required folate.…”
Section: Discussionmentioning
confidence: 99%